Optics in Our Time - Al-Amri, Mohammad D.; El-Gomati, Mohamed; Zubairy, M. Suhail (Springer Nature, 2016)
Optics, Lasers, Photonics, Optical Devices; Quantum Optics; Popular Science in Physics; History and Philosophical Foundations of Physics